Intratumor Microbiome Analysis Identifies Positive Association Between Megasphaera and Survival of Chinese Patients With Pancreatic Ductal Adenocarcinomas - Huang, Yu; Zhu, Ning; Zheng, Xing; Liu, Yanhong; Lu, Haopeng; Yin, Xiaochen; Hao, Huaijie; Tan, Yan; Wang, Dongjie; Hu, Han; Liang, Yong; Li, Xinxing; et al. (Frontiers in Immunology, 2022)
Human tumors harbor a plethora of microbiota. It has been shown that the composition and diversity of intratumor microbiome are significantly associated with the survival of patients with pancreatic ductal adenocarcinoma (PDAC). However, the association in Chinese patients as well as the effect of different microorganisms on inhibiting tumor growth are unclear. In this study, we collected tumor samples resected from long-term and short-term PDAC survivors and performed 16S rRNA amplicon sequencing. We found that the microbiome in samples with different survival time were significantly different, and the differential bacterial composition affected the metabolic pathways in the tumor microenvironment. Furthermore, administration of Megasphaera, one of the differential bacteria, induced a better tumor growth inhibition effect when combined with the immune checkpoint inhibitor programmed cell death-1 receptor (anti-PD-1) treatment in mice bearing 4T1 tumor. These results indicate that specific intratumor microorganisms can enhance the anti-tumor effect in the host, laying a foundation for further clarifying the underlying detailed mechanism.